2008
DOI: 10.1128/jvi.02500-07
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Nuclear Antigen 3C Interacts with and Enhances the Stability of the c-Myc Oncoprotein

Abstract: Epstein-Barr virus (EBV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 44 publications
(88 reference statements)
3
81
0
1
Order By: Relevance
“…HEK 293T cells were transfected by electroporation with a Bio-Rad Gene Pulser II electroporator. Briefly, 15 ϫ 10 6 cells harvested in exponential phase were collected, washed in phosphate-buffered saline (PBS), and resuspended in 400 l of the appropriate medium without serum containing DNA for transfection (3,35). Resuspended cells were transferred to an 0.4-cmgap cuvette, and electroporation was performed at 975 F and 210 V for HEK 293T cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HEK 293T cells were transfected by electroporation with a Bio-Rad Gene Pulser II electroporator. Briefly, 15 ϫ 10 6 cells harvested in exponential phase were collected, washed in phosphate-buffered saline (PBS), and resuspended in 400 l of the appropriate medium without serum containing DNA for transfection (3,35). Resuspended cells were transferred to an 0.4-cmgap cuvette, and electroporation was performed at 975 F and 210 V for HEK 293T cells.…”
Section: Methodsmentioning
confidence: 99%
“…pA3M or pA3F-EBNA3C constructs express either full-length EBNA3C or different truncated versions of EBNA3C with either a Myc tag or a Flag tag at the carboxy-terminal end, as described previously (3,37). Glutathione S-transferase (GST)-EBNA3C truncation mutants have been previously described (3). The C143N point mutation in the EBNA3C gene was prepared by a standard PCR primer mutagenesis method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of earlier studies have successfully established that EBNA3C, an indispensable oncoprotein required for EBV-mediated B-cell transformation, strongly interferes with the functions of many important cellular proteins which are principally involved in cell cycle checkpoints at both the G 1 -to-S and G 2 -to-M transitions (1,6,7,22). Recently, in an initial study, we clearly showed that EBNA3C directly interacts with p53 and efficiently blocks its transcriptional as well as apoptotic activities (23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EBNA3C interacts with a vast range of transcriptional modulators, including PU.1, Spi-B, HDAC1, CtBP, DP103, p300, prothymosin-␣, Nm23-H1, SUMO1, and SUMO3 (15,22,23). EBNA3C also plays a critical role in deregulating the mammalian cell cycle by targeting several cellular oncoproteins and tumor suppressors (1,7,8). Recently, we have shown that EBNA3C directly binds to p53 tumor suppressors and represses their apoptotic and transcriptional activities (23).…”
mentioning
confidence: 99%